Depictions of older adults residing in nursing homes: a Goffman-inspired thematic analysis of children’s picture books in a Danish context - Glasdam, Stinne; Gulestø, Ragnhild Julante Andersen; Stilwell, Christie (Frontiers in Sociology, 2025)
IntroductionSome children may witness their grandparents or great-grandparents spending their final days in a nursing home, while others have peers with older relatives living in nursing homes. Children learn about ageing through experience and exposure, where picture books can also shape their perceptions and attitudes toward older adults residing in nursing homes.AimTo explore the underlying beliefs and attitudes about ageing and older adults residing in nursing homes depicted in children’s picture books in a Danish context.MethodsA systematic search of children’s picture books was conducted in the national Danish library catalogue. The search strategy initially identified 360 books, all were manually screened against the inclusion and exclusion criteria. In total, 22 met the inclusion criteria. Data were extracted and analysed using a descriptive and reflexive thematic analysis, methodologically inspired by Braun and Clarke and theoretically informed by Goffman.ResultsThe empirical material consisted of 439 pages containing text and/or illustrations depicting nursing homes and/or older adults living in them. The first editions were published between 1973 and 2022, with all books (re)printed in Denmark after 1975. The books originated from nine countries, with the majority from Denmark (n = 9). Three overarching themes were constructed: “Nursing homes—a housing solution between necessity and coercion,” “Associations between nursing homes and kindergartens,” and “The present was the past and death was the future.” Nursing homes were depicted both as care facilities and places of forced residence, often akin to kindergartens and reinforcing the infantilization of older adults. Older adult characters were often depicted as equals to children, while the middle generation functioned as a bridge between generations without much interaction with older adults. Few books addressed death directly, and those that did tended to portray it in romanticized terms, surrounded by a nuclear family.ConclusionPicture books reinforced certain stereotypes about nursing homes, older adults, and family dynamics. Future publications should consider ways to integrate realistic and diverse depictions of nursing homes, their residents, and friends and family that visit.